2007
DOI: 10.1029/2006jb004511
|View full text |Cite
|
Sign up to set email alerts
|

The40Ar/39Ar age constraints on the duration of resurgence at the Valles caldera, New Mexico

Abstract: The 40Ar/39Ar ages for rocks from the Valles caldera, New Mexico, imply that resurgent uplift of the caldera floor occurred within 27 ± 27 ka of caldera collapse. The structural resurgent dome of the Valles caldera was uplifted approximately 1000 m above the surrounding caldera floor during resurgence. The upper Bandelier Tuff, which yields an age of 1.256 ± 0.010 Ma (2σ; ages relative to Fish Canyon tuff sanidine at 28.02 Ma), is the lower constraint on the timing of resurgence. The oldest postcollapse ring f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 49 publications
1
63
1
Order By: Relevance
“…There were only ~5000 years between the Oruanui eruption and the first dacite eruption, a gap that is within the uncertainties of the age determinations of many worldwide Quaternary large silicic eruptions. At Valles caldera, New Mexico, the 1.25 Ma Bandelier eruption was rapidly followed by large-scale structural resurgence and post-caldera volcanism with low-silica rhyolite ring plain domes erupting 27 ± 27 kyr after the eruption (Phillips et al 2007). For the 767 ka Bishop Tuff eruption at Long Valley, the post-caldera environment was dominated by both voluminous magmatic (>100 km 3 ) and structural resurgence.…”
Section: Summary Of Taupo's Magmatic System Through Timementioning
confidence: 99%
“…There were only ~5000 years between the Oruanui eruption and the first dacite eruption, a gap that is within the uncertainties of the age determinations of many worldwide Quaternary large silicic eruptions. At Valles caldera, New Mexico, the 1.25 Ma Bandelier eruption was rapidly followed by large-scale structural resurgence and post-caldera volcanism with low-silica rhyolite ring plain domes erupting 27 ± 27 kyr after the eruption (Phillips et al 2007). For the 767 ka Bishop Tuff eruption at Long Valley, the post-caldera environment was dominated by both voluminous magmatic (>100 km 3 ) and structural resurgence.…”
Section: Summary Of Taupo's Magmatic System Through Timementioning
confidence: 99%
“…Available time constraints suggest uplift occurred over durations of 10 4 -10 5 years (Smith and Bailey, 1968;Marsh, 1984) at average rates much lower than those for the restless calderas mentioned above. For instance, for the Upper Bandelier Tuff (UBT) caldera cycle at the Valles Caldera, New Mexico, Phillips et al (2007) found that post collapse volcanism commenced shortly (unresolvable time lag) after caldera collapse and resurgent uplift occurred over a duration of 27 ± 27 ka, or <54 ka calculated from the difference in the 40 Ar/ 39 Ar ages of sanidine from the UBT 1.256 ± 0.010 Ma and the Cerro del Medio dome 1.229 ± 0.017 Ma (the oldest post collapse dome). An average rate of uplift was calculated at ∼1.9 cm/year, although an arbitrary duration of 1000 years could be used to suggest rates of 100 cm/year (Phillips et al, 2007 end of their page 10).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, for the Upper Bandelier Tuff (UBT) caldera cycle at the Valles Caldera, New Mexico, Phillips et al (2007) found that post collapse volcanism commenced shortly (unresolvable time lag) after caldera collapse and resurgent uplift occurred over a duration of 27 ± 27 ka, or <54 ka calculated from the difference in the 40 Ar/ 39 Ar ages of sanidine from the UBT 1.256 ± 0.010 Ma and the Cerro del Medio dome 1.229 ± 0.017 Ma (the oldest post collapse dome). An average rate of uplift was calculated at ∼1.9 cm/year, although an arbitrary duration of 1000 years could be used to suggest rates of 100 cm/year (Phillips et al, 2007 end of their page 10). Given the uncertainties in the ArAr age data used at Valles, it would be reasonable to suggest that rates anywhere between the two values are permissible.…”
Section: Introductionmentioning
confidence: 99%
“…The Precambrian basement is unconformably overlain by Paleozoic and Mesozoic sedimentary rocks, which were intruded by monzonite and diorite porphyry during the Paleogene (K-Ar ages are 25-28 Myr; Ross, 2006). The laccolithic structures preserve Mesozoic rocks at the mountain flanks, mainly clays and sandstones (Richmond, 1962;Henning, 1975). Within the adjacent Paradox Basin, the Mesozoic rock sequence is underlain by marine sediments, which include limestone, dolomite, slate, and a several-hundreds-of-meters-thick diapiric layer of salt and gypsum (Henning, 1975).…”
Section: La Sal Mountains Utahmentioning
confidence: 99%